Cover Image. Issue 5 (1st March 2023) - Sakamoto, Shinnichi; Ide, Fumio; Hoshino, Miyako; Nishimura, Michiko; Kusama, Kaoru; Kikuchi, Kentaro
Abstract : The cover image is based on the Original Article A new insight into the histogenesis and morphogenesis of Warthin tumour: significance of intranodal excretory duct inclusions by S Sakamoto et al., https://doi.org/10.1111/his.14866 .